2011
DOI: 10.1017/s0031182011000710
|View full text |Cite
|
Sign up to set email alerts
|

CrATP interferes in the promastigote-macrophage interaction inLeishmania amazonensisinfection

Abstract: Recent have shown the relationship between Ecto-Nucleoside-Triphosphate-Diphosphohydrolases (Ecto-NTPDases or ecto-nucleotidases) and virulence and infectivity in trypanosomatids. In this work, the inhibition of the ecto-ATPase activities and promastigote growth of Leishmania amazonensis by CrATP was characterized. Furthermore, this compound was used to investigate the role of ecto-nucleotidase in the interaction of L. amazonensis with resident peritoneal macrophages obtained from BALB/c mice. CrATP partially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…There are lines of evidence that NTPDases are related to virulence and infectivity in protozoan parasites [19][20][21][22][23]. However, most of the studies reported ecto-NTPDase enzymatic activities in intact parasites or plasma membrane fractions.…”
Section: Resultsmentioning
confidence: 99%
“…There are lines of evidence that NTPDases are related to virulence and infectivity in protozoan parasites [19][20][21][22][23]. However, most of the studies reported ecto-NTPDase enzymatic activities in intact parasites or plasma membrane fractions.…”
Section: Resultsmentioning
confidence: 99%
“…This activity is important to the organism because these parasites do not have the ability to perform de novo purine synthesis, allowing them to acquire nucleosides. Furthermore, there is a hypothesis that ecto-NTPDases could act as adhesion molecules that facilitate parasitic infection (48). Furthermore, there is a hypothesis that ecto-NTPDases could act as adhesion molecules that facilitate parasitic infection (48).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the ability to cleave ATP, a pro-inflammatory molecule, and to generate adenosine, an anti-inflammatory molecule, is involved in the regulation of the immune response triggered by the parasite Leishmania (47). Furthermore, there is a hypothesis that ecto-NTPDases could act as adhesion molecules that facilitate parasitic infection (48). Our results showing that oATP impaired ecto-ATPase activity in macrophages with a less pronounced effect on Leishmania and the previously demonstrated reduction in in vitro and in vivo infectivity of Leishmania promastigotes maintained for a long period in axenic culture are both associated with reduced hydrolytic activity of ATP and ADP (49), and suggest that the activity of these enzymes may be a virulence factor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the adhesion and endocytic indices were significantly reduced when the promastigotes were treated with CrATP before the interaction with BALB/c peritoneal macrophages, suggesting that the ecto‐ATPase exerts a crucial role in the macrophage invasion process. Interestingly, washing the CrATP‐treated promastigotes before the interaction assay restored the endocytic and adhesion indices (Ennes‐Vidal et al, ).…”
Section: Leishmania Amazonensis Ntpdasesmentioning
confidence: 98%